Answer:
The 2 values that makes the function equal to 18 is 3 and -6
Explanation:
First you can convert the quadratic equation from standard form to root form
Step 1: Substitute f(g) = 18
Step 2: Move 18 to the other side to create
0 = g² + 3g - 18
Step 3: Now we rearrange equation from standard form into root form
Step 4: Find what adds to 3 and multiples to -18
-3 and 6 adds to 3 and multiples to -18
Step 5: Now we substitute -3 and 6 into the root equation
0 = (g-3)(g+6)
Step 6: Set the brackets to 0 and solve
g - 3 = 0
g = 3
g + 6 = 0
g = -6